The Integration Of Reason And Revelation In Islamic Educational Philosophy As The Epistemological Foundation Of Islamic Education - Siti Nurhayati; Weny Alpina; Rizka Putri Susilo Ningrum; Khoiriyah (Al-Hikmah: International Journal of Islamic Studies, 2026)
This study aims to examine the integration of reason and revelation in Islamic educational philosophy as the epistemological foundation of Islamic education. This inquiry is motivated by the tendency of modern education to separate rationality from transcendental values, a condition that potentially leads to moral and spiritual crises. This research employs a qualitative approach using a library research design. The data are derived from primary and secondary sources, including the Qur’an, hadith, as well as classical and contemporary works relevant to Islamic educational philosophy. Data analysis is conducted through descriptive-analytical and interpretative methods. The findings indicate that reason and revelation in Islam maintain an integrative and complementary relationship. Reason functions as a rational instrument for understanding and developing knowledge, while revelation serves as a source of normative truth that guides and regulates the operation of reason. The integration of reason and revelation rejects the dichotomy between religious and secular sciences and affirms that all knowledge ultimately originates from Allah SWT. This study concludes that the integration of reason and revelation constitutes an essential epistemological foundation in Islamic education for the formation of insān kāmil, characterised by a balanced development of intellectual, spiritual, and moral dimensions.